Commercial Bank Lending to Small and Medium Scale Enterprises and Nigeria Economy - OLAOYE, Clement Olatunji; ADEDEJI, Ayodeji Quadri; AYENI-AGBAJE, Rafiat Abiodun (Journal of Accounting, Business and Finance Research, 2018)
The study examined the commercial bank lending to Small and Medium Scale Enterprises and Nigeria economy over a period of twenty years, spanning from 1998 to 2017. Specifically the study analyzed the effect of Average commercial bank lending rate, commercial bank loans and inflation rate to SMEs growth on Nigeria economy, and also the causal relationship between explanatory variables and Nigeria economy measured in terms of GDP. The study made used of secondary data sourced from the Central Bank of Nigeria Statistical Bulletin and the National Bureau of Statistics for the period under study. Data collated were analyzed with descriptive analysis, correlation analysis, ordinary least squares regression analysis, and Granger causality analysis. The findings revealed that commercial bank loans to SMEs (CBLSMES) had a negative and insignificant impact on a gross domestic product with a coefficient estimate of -1.015926 (p=0.0167 < 0.05). Average commercial bank lending rate to SMEs (ACBLRSMES) had a negative and insignificant impact on a gross domestic product with a coefficient estimate of -1911.581 (p=0.6178 > 0.05). Meanwhile, the study revealed that inflation rate (IFTRATE) exert an insignificant positive impact on a gross domestic product with a coefficient estimate of 1833.262 (p=0.2400> 0.05). The result also revealed that there is no causal relationship between exploratory variables (commercial bank loans to SMEs, Average commercial bank lending rate to SMEs, inflation rate) and Nigeria economy measured in terms of GDP and while ACBLRSMES and CBLSMES has a causal relationship to SMEs. The study recommend that in order to address Nigeria government should recognize the impact of SMEs in Nigeria economy and attach importance to the growth of SMEs by encouraging banks to assist with loans because it constitutes a major tool in boosting employment in the country.